PENGARUH BRAND AWARENESS DAN BRAND ASSOCIATION TERHADAP BRAND LOYALTY MELALUI PERCEIVED QUALITY PADA SEPATU MERK NIKE DI SURABAYA - Sanjaya, Benny (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The famous and trusted brand is an invaluable asset. After determining the brand, the company had to build the brand into a brand that has a high equity. High brand equity is influenced by four main elements of brand equity, brand awareness, perceptions of quality, brand association, and brand loyalty. The research aims to know the influence of brand awareness, brand association,, the brand loyalty of brand Nike shoes in Surabaya with perceived quality as an intervening variable. In this study used is the conclusive research on the study of experimental or causal research. Samplingtaking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 consumer brand Nike shoes in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that brand awareness, and brand image effect directly against the perceived quality, and indirectly to the brand loyalty by using the quality perceived as intervening variable. The research also found that perceived quality to brand loyalty.